MENINGKATKAN KEMAMPUAN GERAK GALOMBANG RANDAI MELALUI STRATEGI COOPERATIVE LEARNING DI KELAS X5 DI SMA N 1 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Yosilva Andres; Yuliasma Yuliasma; Afifah Asriati (FBS Universitas Negeri Padang, 2017)
AbstractThis article the aim to investigate the implementation of cooperative learning strategy in grade X5 in learning dance at SMAN 1 Pulau Punjung Dharmasraya District.This research wa a Classroom Action Research (CAR). The objects of this research were student in X5 in SMAN 1 Pulau Punjung which consisted of 26 students. The instruments of this research were the researcher as the observer and several aids such as observation sheet and learning outcome instrument. The data were collected through observation, documentation, and achievement test, furthermore, the data were collected by using data analysis techniques to select and analyze its validity. Findings of this research indicate that the implementation of cooperative learning strategy in SMAN 1 Pulau Punjung was effective and succesful during 2 cycles with 6 meeting each. Student were motivated to learn it could be seen from the learning goals of traditional dance that had been acheved in the aspects of physical, rhytim and sense assessment. The average score of students learning outcomes in cycle I was 68,8and it increased in cycle II which was 87,5. It can be said that this research was conducted well since the use of cooperative learning strategyin learning dance at SMA N 1 Pulau Punjung Dharmasraya District improved students’ ability in Galombang motion.Keywords: Learning outcomes, Method, Dance